Effects of intracarotid injection of methylprednisolone on cellular oedema after osmotic opening of the blood-brain barrier in rats - Kozler, P; Pokorný, J (Prague medical report, 2004)
In our work we studied methylprednisolone (MP) for its effects on the permeability of cytoplasmatic membranes of neuronal populations in the rat. We used a standard model of cellular oedema induced by water intoxication, applying MP selectively into the internal carotid (ICA) after opening the blood-brain-barrier (BBB) with mannitol. The results were assessed under fluorescence microscopy in keeping with the Intracellular Distribution Index of Evans Blue (IDI) in the neocortical field (Cortex) and in hippocampal areas CA1, CA3 and GD. Evans blue (EB) was applied similarly as MP Three different experiments were carried out. In experiment 1--EB alone and no MP was applied. In experiment 2--5.4 mg/kg MP and EB were applied. In experiment 3--54 mg/kg MP and EB were applied. In experiment 1 the IDI values were high (>1), indicating the presence of large quantities of EB in the cells. In experiments 2 and 3 the IDI values were low (<1), indicating more EB outside than inside cells. IDI differences between experiments 2 and 1 and experiments 3 and 1 were statistically significant (p<0.05). This morphological evidence sufficiently proved the possibility to restore the cell membrane integrity by means of MP administration.
Keywords: buněčná membrána; edém mozku; mozek; Humans; neuroprotektivní látky; hematoencefalická bariéra; Injections, Intra-Arterial; Blood-Brain Barrier; krysa rodu Rattus; Brain Edema; lidé; zvířata; Neuroprotective Agents; osmolární koncentrace; potkani Wistar; mannitol; Rats, Wistar; methylprednisolon; Carotid Artery, Internal; Brain; Mannitol; arteria carotis interna; Methylprednisolone; Rats; Animals; Cell Membrane; injekce intraarteriální; Osmolar Concentration